One-Stage versus two-stage arteriovenous loop reconstructions - Henn, Dominic; Wähmann, Matthias Stefan Theodor; Horsch, Miriam; Hetjens, Svetlana; Kremer, Thomas; Gazyakan, Emre; Hirche, Christoph; Schmidt, Volker-Jürgen; Germann, Günter; Kneser, Ulrich (Plastic and reconstructive surgery, 2019)
Background:The optimal time for flap anastomosis to an arteriovenous loop remains controversial. Whether perforator flaps and axially vascularized muscle or fasciocutaneous flaps lead to comparable outcomes in conjunction with arteriovenous loops has not been investigated.Methods:Medical records fro
Gesehen am 01.04.2019